Using local resources: barefoot doctors and bone manipulation in rural Langzhong, Sichuan Province, PRC - Lora-Wainwright, A (Brill, 2005)
This article offers an account of two local options for healing available in contemporary rural Sichuan. Since the recent economic reforms, available healthcare options have multiplied due to social, economic and cultural changes. Yet, rising costs have entailed a narrowing of resources accessible to rural peasantry. In this context, research on the use of local alternatives becomes paramount. The barefoot doctor and bone manipulator discussed below offer accessibly healthcare without conspicuously compromising its quality. Their position as members of the local community and experienced healers, who have been practising for over 30 years, enhances faith in their healing powers. A study of these practitioners offers insights into how local people evaluate their services, and highlights the importance of assessing their practice in the terms used by the locals themselves. Case studies drawn from fifteen months of research and experience of living in rural China illustrate that medical choices are situational, strategic and performative. Apparent inconsistencies between villagers' claims and daily practices become intelligible in light of the wider challenges they face. Indeed, evaluation of local healers cannot be divorced from peasants' experience of the cultural, social and economic setting. Focusing on the sufferers' own understanding, feelings and practices surrounding illness and health allows us to appreciate how efficacy is discussed, evaluated and established. In turn it highlights the continuing importance of local healing alternatives.